CURRENT STATUS AND PROBLEMS OF DEVELOPMENT OF CONSUMER COOPERATIVES IN CONDITIONS OF ECONOMIC TRANSFORMATION - E. Belyaeva; O. Prikhodchenko (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the features of consumer cooperation organizations, problems and main directions of development. The study focuses on the factors of macro-and micro-level, contributing to the development of the crisis of consumer cooperation organizations. The article analyzes the organizational structure of consumer cooperation of the Central Union of the Russian Federation, the results ofproduction and procurement activities, as well as the reasons for the decline in efficiency. A special place in the article is devoted to the evaluation of protectionist measures aimed at supporting consumer cooperation at the regional level. On the basis of the analysis the directions of improving the activity of consumer cooperation in terms of economic transformation, in particular through the implementation of the priority regional project in the framework ofproject management.